Introduction to post-Keynesian economics - Lavoie, Marc (New York Palgrave Macmillan, 2009)
"​This book offers an accessible introduction to post-Keynesian economics, showing that there is an alternative to neoclassical economics and its free-market economic policies. Post-Keynesian economics is founded on realistic assumptions, such as interest targeting by central banks or constant average variable costs in manufacturing and services". (from Amazon page)
Introduction -- 1 Post-Keynesian heterodoxy -- 2 Heterodox microeconomics -- 3 A macroeconomic monetary circuit -- 4 The short period: effective demand and the labour market -- 5 The long period: old and new growth models --  6 General conclusion
Includes bibliographical references ( p: 133-141) and Index.
Keywords: Economics; ECONOMICS; KEYNESIAN ECONOMICS; MACROECONOMICS